The United States Foreign Policy in the Middle East from 11/09/2001-2017: Comparative Study - Bencheikh, Khaoula (2020)
Foreign policy is commonly known as the rules or plans which is applied by a leader power; such as the United States; in order to keep the other countries under its political, economical, ideological control. Since, the emergence of the United States as the only power in this world the geopolitics of the world was changed and the globalization had covered the world. The United States used many faces and types of foreign policy such as orientalism and protectionism. It chooses the suitable foreign policy according to the national stability of the region which will be controlled and its interests in that region. This study sheds the light on the United States foreign policy in the three Middle East countries: Syria, Iraq and Palestine, in two ruling periods which are: George Bush ruling period (2001_2009) and Barack Obama ruling period (2009_2017).This study investigates two main questions: What is the relationship between the United States and the Middle East before 11/09 attacks? And what is the main United States foreign policies used in the two periods in the three countries? Also, this study gives two hypotheses. The first one is the relationship between the Middle East and the United States was a hostile relationship, and the other one is that the United States used protectionism in the two periods.